Low-resistance carbon-plastic composite polar plate as well as preparation method and application thereof

By mixing nanoresin and carbon-based materials through air convection, low-resistance carbon-plastic composite plates are prepared by hot pressing process, which solves the problems of high resistivity and poor durability of carbon-plastic composite plates, and achieves the improvement of conductivity and interlayer toughness. , improves the power density and heat-resistant aging performance of the battery.

CN119297299AActive Publication Date: 2025-01-10SHANDONG DINGYU NEW ENERGY MATERIALS CO LTD

Patent Information

Application Number
CN202411564463.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-10
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The resistivity of the carbon plastic composite electrode plate is high, resulting in a lack of conductive effect, a large amount of heat is generated during the discharge process, which can easily lead to the failure of the proton exchange membrane, and may cause fine cracks and bending deformation under the action of temperature and stress.

Method used

Mixing nanoresin and carbon-based materials through air convection, low-resistance carbon-plastic composite electrode plates are prepared by hot pressing process. The specific particle size of the nanoresin and carbazole units are introduced to improve the bonding interface strength and thermal stability, and adjust the electronics of the carbon material. properties, reducing resistivity and permeability.

Benefits of technology

It achieves low resistivity, improves conductivity and interlayer toughness, reduces fine cracks and bending deformation, and improves the power density and heat-resistant aging performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118847830000041
    Figure BDA0005118847830000041
  • Figure BDA0005118847830000071
    Figure BDA0005118847830000071
Patent Text Reader

Abstract

The invention belongs to the field of flow batteries, and particularly discloses a low-resistance carbon-plastic composite polar plate and a preparation method and application thereof.According to the low-resistance carbon-plastic composite polar plate and the preparation method and application thereof, uniform mixing of a carbon material and nano resin is achieved through air convection, the nano resin can be stacked on the surface and interlayer of the carbon material in order, expansion and rebound in the mold pressing process are improved, and the stability of the carbon-plastic composite polar plate is improved. The carbon-plastic composite polar plate has the advantages that the carbon-plastic composite polar plate is prepared from the carbazole unit, the volume effect of the formed polar plate and the generation of microcracks are inhibited, a continuous conductive and heat-conducting filler network can be formed, the carbon-plastic composite polar plate has low resistivity and conductivity, and the nano resin containing the carbazole unit has high thermal stability and is not easy to age in a battery environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of liquid flow batteries, and specifically relates to a low-resistance carbon-plastic composite plate and a preparation method and application thereof. Background Art

[0002] As the core component of the flow battery, the plate mainly isolates the positive and negative ions of adjacent batteries and transfers current and heat. However, in the actual operation of the battery, the plate also needs to have excellent bending and compressive strength, air tightness, hydrophobicity and corrosion resistance. At the same time, in order to improve the power density of the battery and reduce production costs, the plate should be as light and thick as possible while ensuring the normal operation of various functions. The types of plates can be mainly divided into: graphite plates, metal plates and composite plates according to the material. Among them, carbon-plastic composite plates are a new type of composite material. It is made of graphite and polymer resin. It has the advantages of simple process, easy forming, sufficient raw materials and low production cost. It can use molding to carve flow channels on the plate instead of complex processing. Therefore, it has received widespread attention.

[0003] The processing performance and structural strength of carbon-plastic composite plates are significantly better than those of hard graphite plates, and their liquid resistance is also better than that of flexible graphite plates. In addition, their corrosion resistance is much stronger than that of ordinary metal plates. These characteristics make carbon-plastic composite plates widely used. However, the resistivity of carbon-plastic composite plates is usually 1 to 2 orders of magnitude higher than that of metal plates and graphite plates, resulting in a lack of conductive effect; and due to the high resistance, a large amount of heat will inevitably be generated during the discharge process, which will increase the battery temperature and easily lead to the failure of the proton exchange membrane.

[0004] Patent CN114976086B discloses a composite graphite bipolar plate and a preparation method. The electrical conductivity, thermal conductivity and hydrogen barrier of the composite graphite plate are improved by grafting modified graphene with thermosetting azidophenolic resin; and the compatibility of the conductive filler and the resin is improved by solvent-free hot pressing and curing the powder, thus avoiding the problem of local expansion of the plate caused by the direct hot pressing process. However, the azidopolymer product may cause problems such as a widening of the molecular weight distribution and uncontrollable molecular chain end groups, which may cause the plate to have fine cracks, bending deformation and other problems during the operation of the battery stack due to repeated changes in temperature and force. Summary of the invention

[0005] In order to overcome the deficiencies of the above-mentioned prior art, the present application provides a low-resistance carbon-plastic composite plate and a preparation method thereof. The carbon-plastic composite plate has a low resistivity, effectively improves the conductivity and interlayer toughness of the composite material, thereby solving problems such as fine cracks and bending deformation that may occur during the use of the battery.

[0006] In order to achieve the above purpose, the technical solution adopted in this application is:

[0007] The first aspect of the present application provides a method for preparing a low-resistance carbon-plastic composite plate, comprising the following raw materials: mixing a nano-resin and a carbon-based mixture by air convection to obtain a mixture; spreading powder and pre-pressing to obtain a blank plate; and then hot-pressing the blank plate to obtain the low-resistance carbon-plastic composite plate.

[0008] Preferably, the mass ratio of the nano resin to the carbon-based mixture is (0.18-0.32):1.

[0009] The present application mixes the carbon material and the resin by air convection, so that the nano resin can be stacked on the surface and between the layers of the carbon material in an orderly manner, thereby achieving uniform mixing of the graphite powder and the adhesive resin, which is convenient for subsequent powder spreading.

[0010] In some embodiments, the specific operation of hot pressing is: first hot pressing for 3-5 minutes at a hot plate temperature of 240-280°C and a pressure of 8-14 MPa; then hot pressing for 2-4 minutes at a hot plate temperature of 180-220°C and a pressure of 15-22 MPa; then, at this temperature, molding the flow channel; finally, cooling to room temperature and demolding.

[0011] In some embodiments, the particle size of the nanoresin is 70-120 nm.

[0012] In some embodiments, the preparation steps of the nano resin are as follows:

[0013] S1, stirring N-methylpyrrolidone and sodium sulfide at 150-180°C for 20-40 min, adding p-dichlorobenzene, p-dichlorobenzoic acid and sodium hydroxide, passing nitrogen, first heating to 200-240°C and keeping warm for 1-4 h, then heating to 260-280°C and keeping warm for 1-3 h, cooling to room temperature, acidifying, washing, filtering and vacuum drying to obtain reactant 1;

[0014] S2. Under nitrogen protection, dichloromethane, aluminum chloride and 3,6-di[9-carbazolyl]-9-phenylcarbazole are stirred at 30-60° C. for 12-17 hours, and then reactant 1 obtained in step S1 is added and stirred for 8-12 hours. After cooling to room temperature, the mixture is filtered, washed, recrystallized and vacuum dried. The nano resin is obtained by vacuum drying.

[0015] In some embodiments, the mass ratio of sodium sulfide to p-dichlorobenzene in step S1 is 1:(0.73-0.98).

[0016] In some embodiments, in step S2, the mass ratio of aluminum chloride, 3,6-di[9-carbazolyl]-9-phenylcarbazole and reactant 1 is (9.2-11.8):1:(8.71-10.05).

[0017] The present application obtains a nano resin of a specific particle size through a specific process. The nano resin, on the one hand, solves the problem of poor impregnation between the carbon-based mixture and the thermoplastic resin, improves the strength of the bonding interface, and reduces the difficulty and cost of production; on the other hand, the thermal stability of the polymer is enhanced by introducing the carbazole unit, thereby avoiding the formation of a conjugated structure between the unsaturated S atoms in the resin molecule and the benzene ring on the molecular chain, and increasing the difficulty of the sulfide bonds in the macromolecule being oxidized to sulfoxide and sulfone groups, thereby ensuring that the main chain is not easy to break and the resin is not easy to age in the battery environment; on the third hand, through the interaction between the polymer skeletons, the microporosity of the polymer formed by the self-polymerization of the carbazole unit is reduced, and at the same time the permeability of the plate is reduced, so that it does not need to be plugged, which helps to improve the power density of the battery.

[0018] In some embodiments, the carbon-based mixture comprises graphite, graphene, and multi-walled carbon nanotubes.

[0019] In some embodiments, the mass ratio of the graphite, graphene and multi-walled carbon nanotubes is 1:(0.1-0.3):(0.05-0.25).

[0020] The carbon-based mixture of the present application can form a complete conductive network in the composite plate through the specific selection of multiple carbon-based material types and proportions. However, during the operation of the battery stack, the plate may have problems such as fine cracks, bending and deformation due to repeated changes in temperature and force. After the nano-resin in the present application is mixed with the carbon-based mixture, a part of it is distributed between the carbon material layers, which can improve the expansion and rebound during the molding process, and at the same time can inhibit the volume effect of the molded plate and the generation of microcracks.

[0021] In order to improve the conductivity of carbon-plastic composite plates, a common method is to increase the amount of carbon-based materials used. However, high amounts of carbon-based materials will cause a significant decrease in the material's processing properties and mechanical properties. The electron-withdrawing properties of S atoms in the nano-resin in this application are beneficial for adjusting the electronic properties of carbon materials, making it easier to polarize electron pairs and generate charge positions, thereby achieving the purpose of improving electrochemical performance.

[0022] The second aspect of the present application provides a low-resistance carbon-plastic composite plate, wherein the resistivity of the composite plate is 1.6-3.4 mΩ.cm 2 .

[0023] The third aspect of the present application provides an application of a low-resistance carbon-plastic composite electrode plate in a liquid flow battery and a fuel cell.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present application provides a low-resistance carbon-plastic composite plate, which uses air convection to enable nano-resin to be stacked in an orderly manner on the surface and between layers of the carbon material, thereby improving expansion and rebound during the molding process and suppressing the volume effect and microcracks of the molded plate.

[0026] 2. The present application enhances the thermal stability of the polymer by introducing carbazole units into the nano-resin, thereby avoiding the formation of a conjugated structure between the unsaturated S atoms in the resin molecules and the benzene rings on the molecular chain, increasing the difficulty of the sulfide bonds in the macromolecules being oxidized to sulfoxide and sulfone groups, ensuring that the main chain is not easily broken and making the resin not easily aged in the battery environment.

[0027] 3. The nano-resin of the present application reduces the microporosity of the polymer formed by the self-polymerization of the carbazole unit through the interaction between the polymer skeletons, and at the same time reduces the permeability of the plate, so that it does not need to be plugged, which helps to improve the power density of the battery.

[0028] 4. This application optimizes the process of improving the conductivity of carbon-plastic composite plates, and adjusts the electronic properties of carbon materials through the electron-withdrawing characteristics of S atoms in nano-resins, making it easier for carbon materials to polarize electron pairs and generate charge positions, thereby achieving the purpose of improving electrochemical performance. DETAILED DESCRIPTION

[0029] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0030] Preparation Example 1

[0031] The preparation steps of nano resin-A are as follows:

[0032] S1. Stir 500 mL of N-methylpyrrolidone and 100 g of sodium sulfide at 160° C. for 30 min, add 85.13 g of p-dichlorobenzene, 7 g of p-dichlorobenzoic acid and 2.5 g of sodium hydroxide, pass nitrogen, first heat to 220° C. and keep warm for 3 h, then heat to 270° C. and keep warm for 2 h, cool to room temperature, adjust the pH to 6±0.2, wash with deionized water, filter, and vacuum dry at 60° C. to constant weight to obtain reactant 1;

[0033] S2. Under nitrogen protection, 80 mL of dichloromethane, 108 g of aluminum chloride and 10 g of 3,6-di[9-carbazolyl]-9-phenylcarbazole were stirred at 40° C. for 15 h, and then 93 g of the reactant 1 obtained in step S1 was added and stirred for 10 h. After cooling to room temperature, the mixture was filtered, and the filter cake was washed with 1 M hydrochloric acid and deionized water in turn, recrystallized, and vacuum dried at 80° C. to constant weight to obtain nanoresin-A.

[0034] Preparation Example 2

[0035] The preparation steps of nano resin-B are as follows:

[0036] The difference between this preparation example and preparation example 1 is that 70 g of p-dichlorobenzene is used in step S1.

[0037] Preparation Example 3

[0038] The preparation steps of nano resin-C are as follows:

[0039] The difference between this preparation example and preparation example 1 is that 105 g of p-dichlorobenzene is used in step S1.

[0040] Preparation Example 4

[0041] The preparation steps of nano resin-D are as follows:

[0042] The difference between this preparation example and preparation example 1 is that 13 g of 3,6-di[9-carbazolyl]-9-phenylcarbazole is used in step S2.

[0043] Preparation Example 5

[0044] The preparation steps of nano resin-E are as follows:

[0045] The difference between this preparation example and preparation example 1 is that 8 g of 3,6-di[9-carbazolyl]-9-phenylcarbazole is used in step S2.

[0046]

[0047] Example 1

[0048] A method for preparing a low-resistance carbon-plastic composite plate comprises the following steps:

[0049] The nano resin-A and the carbon-based mixture with a mass ratio of 0.26:1 are mixed by an air convection device to obtain a mixture; the powder is spread and pre-pressed to obtain a blank plate; the blank plate is then hot-pressed at a hot plate temperature of 260°C and a pressure of 11MPa for 4 minutes; then the hot plate temperature is 200°C and a pressure of 18MPa for 3 minutes; then at this temperature, the flow channel is molded; finally, it is cooled to room temperature and demolded to obtain a composite plate;

[0050] Among them, the carbon-based mixture contains graphite, graphene and multi-walled carbon nanotubes in a mass ratio of 1:0.2:0.15.

[0051] Example 2

[0052] A method for preparing a low-resistance carbon-plastic composite plate comprises the following steps:

[0053] The nano resin-A and the carbon-based mixture with a mass ratio of 0.18:1 are mixed by air convection to obtain a mixture; the powder is spread and pre-pressed to obtain a blank plate; the blank plate is then hot-pressed at a hot plate temperature of 240°C and a pressure of 14MPa for 3 minutes; then the hot plate temperature is 180°C and a pressure of 22MPa for 2 minutes; then at this temperature, the flow channel is molded; finally, it is cooled to room temperature and demolded to obtain a composite plate;

[0054] Among them, the carbon-based mixture contains graphite, graphene and multi-walled carbon nanotubes in a mass ratio of 1:0.1:0.05.

[0055] Example 3

[0056] A method for preparing a low-resistance carbon-plastic composite plate comprises the following steps:

[0057] The nano resin-A and the carbon-based mixture with a mass ratio of 0.32:1 are mixed by air convection to obtain a mixture; the powder is spread and pre-pressed to obtain a blank plate; the blank plate is then hot-pressed at a hot plate temperature of 280°C and a pressure of 8MPa for 5 minutes; then the hot plate is hot-pressed at a hot plate temperature of 220°C and a pressure of 15MPa for 4 minutes; then at this temperature, the flow channel is molded out; finally, it is cooled to room temperature and demolded to obtain a composite plate;

[0058] Among them, the carbon-based mixture contains graphite, graphene and multi-walled carbon nanotubes in a mass ratio of 1:0.3:0.25.

[0059] Example 4

[0060] This embodiment provides a method for preparing a low-resistance carbon-plastic composite electrode plate. The specific implementation method is the same as that of Example 1, except that the nano-resin-A is replaced by an equal amount of nano-resin-B.

[0061] Example 5

[0062] This embodiment provides a method for preparing a low-resistance carbon-plastic composite electrode plate. The specific implementation method is the same as that of Example 1, except that the nano-resin-A is replaced by an equal amount of nano-resin-C.

[0063] Example 6

[0064] This embodiment provides a method for preparing a low-resistance carbon-plastic composite electrode plate. The specific implementation method is the same as that of Example 1, except that the nano-resin-A is replaced by an equal amount of nano-resin-D.

[0065] Example 7

[0066] This embodiment provides a method for preparing a low-resistance carbon-plastic composite electrode plate. The specific implementation method is the same as that of Example 1, except that the nano-resin-A is replaced by an equal amount of nano-resin-E.

[0067] Example 8

[0068] This embodiment provides a method for preparing a low-resistance carbon-plastic composite electrode plate. The specific implementation method is the same as that of Example 1, except that the carbon-based mixture contains graphite and graphene in a mass ratio of 1:0.2.

[0069] Example 9

[0070] This embodiment provides a method for preparing a low-resistance carbon-plastic composite electrode plate. The specific implementation method is the same as that of Example 1, except that the carbon-based mixture contains graphite and multi-walled carbon nanotubes in a mass ratio of 1:0.15.

[0071] Example 10

[0072] This embodiment provides a method for preparing a low-resistance carbon-plastic composite electrode plate. The specific implementation method is the same as that of Example 1, except that the carbon-based mixture contains graphene and multi-walled carbon nanotubes in a mass ratio of 1:0.75.

[0073] Performance Testing:

[0074] 1. Resistance test

[0075] The resistance of the composite plate was tested using a four-probe resistance tester (Ricow FT-541SJB, Ningbo, China). Deformation of the sample and dust on the sample surface should be avoided during measurement. At least five positions near the edge and center of the composite plate were selected to calculate the average value.

[0076] 2. Bending strength

[0077] A three-point bending test was performed on the composite plates provided in each embodiment according to the industry standard NB / T 42007-2013 using a mechanical universal testing machine to determine the bending strength of the samples. The loading speed was 0.5 mm / min, the size of the composite plates was 100 mm×10 mm, and the span was 64 mm.

[0078] In order to reflect the heat aging resistance of nano resin, the composite plate was heat treated: the composite plate was placed in a high-temperature electric blast drying oven, heated to 350°C at a rate of 5°C / min, and then aged at a constant temperature for 1 hour, taken out and placed in a dryer to cool to room temperature; then placed in an electric blast drying oven, heated to 350°C at a rate of 5°C / min, and then aged at a constant temperature for 200 hours, taken out and placed in a dryer to cool to room temperature, and the bending strength test was performed again.

[0079] 3. Air permeability test

[0080] Reference standard: NB / T 42007-2013, the test method specifically includes: introducing hydrogen and inert gas at a temperature of (25±1.5)℃ and a pressure of 0.1MPa into the two sides of the fixture gas chamber, respectively, to ensure that the pressure on both sides is balanced (controlled by the precision pressure gauges on both sides), and stabilize for at least 5 hours, then pass the outlet of the inert gas into the gas chromatograph to measure the concentration of the measured gas, and record the chromatogram. Calculate the hydrogen permeability C per unit time and per unit area of ​​the composite plate according to C=q / S;

[0081] Where: q is the gas permeation per unit time, cm 3 / s; S is the effective test area of ​​the permeation pool, cm 2 .

[0082] The test results are shown in Table 1.

[0083] Table 1

[0084]

[0085] It can be seen from the data in Table 1 that the composite plates of Examples 1-3 have lower resistance and permeability, and can effectively exert their conductive properties and gas barrier effects; in addition, they have higher flexural strength, indicating that the interface bonding between the nano-resin and the carbon-based mixture is strong, and the difference in flexural strength before and after heat treatment is small, reflecting the heat aging resistance of the nano-resin in the composite plates.

[0086] Compared with Example 1, the nano-resin used in the composite plates of Examples 4-5 changes the amount of p-dichlorobenzene used in step S1, which causes a significant change in the particle size of the nano-resin, which may cause the nano-resin to self-agglomerate or mix unevenly with the carbon-based mixture, resulting in micro-cracks during the molding process, and then leading to increased resistance and permeability; from the change in flexural strength before and after heat treatment, it can be seen that the micro-cracks that appear in production will further expand after heat treatment, resulting in a decrease in flexural strength.

[0087] Compared with Example 1, the nano-resin used in the composite plates of Examples 6-7 changes the amount of 3,6-di[9-carbazolyl]-9-phenylcarbazole in step S2, which is not conducive to the introduction of the carbazole unit, thereby affecting the thermal stability of the nano-resin and the microporosity of the composite plate, resulting in a decrease in the bending strength of the plate and an increase in the permeability; it can be seen from the permeability that the introduction of an appropriate amount of carbazole units can also improve the gas barrier properties of the plate.

[0088] Compared with Example 1, the composite plates of Examples 8-10 changed the type of carbon material in the carbon-based mixture, resulting in a decrease in electrical conductivity, bending resistance and gas barrier properties.

[0089] The embodiments described above do not impose any form of limitation on the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a low-resistance carbon-plastic composite plate, characterized in that: The method comprises the following steps: mixing the nano resin and the carbon-based mixture by air convection to obtain the mixture; spreading powder and pre-pressing to obtain a blank plate; and then hot-pressing the blank plate to obtain the low-resistance carbon-plastic composite plate.

2. The method for preparing a low-resistance carbon-plastic composite plate according to claim 1, characterized in that: The specific operation of the hot pressing is: first hot pressing for 3-5 minutes at a hot plate temperature of 240-280°C and a pressure of 8-14MPa; then hot pressing for 2-4 minutes at a hot plate temperature of 180-220°C and a pressure of 15-22MPa; then at this temperature, molding the flow channel; finally cooling to room temperature and demolding.

3. The method for preparing a low-resistance carbon-plastic composite plate according to claim 1, characterized in that: The particle size of the nano resin is 70-120nm.

4. The method for preparing a low-resistance carbon-plastic composite plate according to claim 3, characterized in that: The preparation steps of the nano resin are as follows: S1. Stir N-methylpyrrolidone and sodium sulfide at 150-180° C. for 20-40 min, add p-dichlorobenzene, p-dichlorobenzoic acid and sodium hydroxide, pass nitrogen, first heat to 200-240° C. and keep warm for 1-4 h, then heat to 260-280° C. and keep warm for 1-3 h, cool to room temperature, adjust pH to 5-7, wash, filter, and vacuum dry to obtain reactant 1; S2. Under nitrogen protection, dichloromethane, aluminum chloride and 3,6-di[9-carbazolyl]-9-phenylcarbazole are stirred at 30-60° C. for 12-17 hours, and then reactant 1 obtained in step S1 is added and stirred for 8-12 hours. After cooling to room temperature, the mixture is filtered, washed, recrystallized and vacuum dried to obtain the nano resin.

5. The method for preparing a low-resistance carbon-plastic composite plate according to claim 4, characterized in that: The mass ratio of sodium sulfide to p-dichlorobenzene in step S1 is 1:(0.73-0.98).

6. The method for preparing a low-resistance carbon-plastic composite plate according to claim 4, characterized in that: In the step S2, the mass ratio of aluminum chloride, 3,6-di[9-carbazolyl]-9-phenylcarbazole and reactant 1 is (9.2-11.8):1:(8.71-10.05).

7. The method for preparing a low-resistance carbon-plastic composite plate according to claim 1, characterized in that: The carbon-based mixture includes graphite, graphene and multi-walled carbon nanotubes.

8. The method for preparing a low-resistance carbon-plastic composite plate according to claim 7, characterized in that: The mass ratio of the graphite, graphene and multi-walled carbon nanotubes is 1:(0.1-0.3):(0.05-0.25).

9. A low-resistance carbon-plastic composite plate obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The resistivity of the low-resistance carbon-plastic composite plate is 1.6-3.4 mΩ.cm 2 .

10. A low-resistance carbon-plastic composite electrode plate obtained by the preparation method according to any one of claims 1 to 8, and use of the low-resistance carbon-plastic composite electrode plate according to claim 9 in a liquid flow battery.

Citation Information

Patent Citations

  • Preparation method of composite graphite bipolar plate

    CN112290040A

  • Composite bipolar plate material as well as preparation method and application thereof

    CN115295808A

  • Preparation method of metal graphite composite bipolar plate for fuel cell

    CN117183183A

  • Sealing plastic for battery cover plate and preparation process of sealing plastic

    CN117363018A

Cited By

  • High-binding-force injection molding alloy part and preparation method thereof

    CN121227032A